1989
DOI: 10.1073/pnas.86.1.402
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean peptidergic neurons in culture show immediate outgrowth in simple medium.

Abstract: The survival and outgrowth of neurons in culture has usually required conditioning factors. We now report that crustacean neurons, taken from the peptidergic neurosecretory system of the eyestalk of crabs (Cardisoma carnifex) and lobsters (Panulirus marginatus), show immediate outgrowth, sustained for a week or more, in defined medium as simple as physiological saline with glucose and glutamine.The neurons show peptide hormone immunoreactivity that is prominent at growth cones, exhibit differences in form corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
2
22
1
1
Order By: Relevance
“…Bars b, c 50 urn; inset 10 urn. (After Dircksen et al 1988) CHH-producing cultured cells could be identified by immunocytochemistry (Cooke et al 1989) and quantitative hormone determinations in individual cells (Keller et al 1995). A finding worth mentioning is the susceptibility of CHH cells, in Cancer borealis, to inhibition by D-glucose.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bars b, c 50 urn; inset 10 urn. (After Dircksen et al 1988) CHH-producing cultured cells could be identified by immunocytochemistry (Cooke et al 1989) and quantitative hormone determinations in individual cells (Keller et al 1995). A finding worth mentioning is the susceptibility of CHH cells, in Cancer borealis, to inhibition by D-glucose.…”
Section: Introductionmentioning
confidence: 98%
“…Dispersed XO cells have been cultured in vitro, where they show axonal outgrowth and the development of elaborate branching and lamellipodial morphologies. Electrophysiological and morphological studies (e.g., on neurosecretory granule content) have been performed on such cells in culture (Cooke et al 1989;Grau and Cooke 1992;Meyers et al 1992), and LG lamina ganglionaris ; ME, MI, MT medullae externa, interna, and terminalis; SG sinus gland; XO X-organ. Bars b, c 50 urn; inset 10 urn.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them were working with short-term culture. As neuron culture of crustacean is concerned, there were reports about successful culture of the peptidergic neurons of the X-organ and the stomatogastric ganglion from the land crab Cardisoma carnifex (Cooke et al 1989;Graf and Cooke 1990;Grau and Cooke 1992).The cardiac ganglion neurons in shore crab Carcinus maenas not only survived in vitro but also maintained their intrinsic membrane and transmitter response (Saver et al 1999). The culture method of medulla terminalia X-organ from the eyestalks of Chinese mitten crab Eriocheir sinensis had also been developed (Sun et al 2000).…”
Section: Introductionmentioning
confidence: 93%
“…Crab physiological saline (Cooke et al 1989): NaCl 440.0 mmol, KCl 11.3 mmol, CaCl 2 13.3 mmol, MgCl 2 26.0 mmol, Na 2 SO 4 23.0 mmol, HEPES 10.0 mmol, pH adjusted to 7.4 with NaOH. Pentylenetetrazole was obtained from Sigma Chemical Co, (US), while sodium valproate tablets were obtained from a local pharmacy.…”
Section: Solutionsmentioning
confidence: 99%